Analisis Stabilitas Timbunan Tinggi Pada Mortar Busa Menggunakan Metode Elemen Hingga Pada Proyek Pembangunan Jalan Baru Batas Kota Singaraja - Mengwitani - Lalu Arpi Wartoyo; Yudhi Lastiasih; Rakhman Taufik; Izzuddin Ismawanto (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2022)
The new road construction of Bts. Singaraja City to Mengwitani has now carried out Phase I (SC 5-6) in 2019 there is a handling of high embankments using a geogrid, a slope of 1:2 at a height of ± 20 meters. At the construction site of this road there is limited land for Right Of Way (ROW) due to hilly area conditions. To overcome this problem, it is necessary to design a road embankment construction plan from a material that is safe and light enough, lightweight foam mortar embankment has been found as an alternative method to protect against overload to the ground, with lightweight structural materials and high compressive resistance to support the load. traffic. Based on the current conditions, an analysis of the stability of the light embankment of foam mortar will be carried out as an alternative for handling high embankments with variations of the vertical slope, 1:1, 1:2 and 1:3, an analysis of the stability of the embankment using the Plaxis application. The results of the analysis show that the greater the slope used, the greater the safety factor that occurs. Based on the results of the analysis, the variation of the slope of the upright embankment collapses so that there is no safety factor